Luminescence characteristics of muddy sediments in the turbidity maximum zone of the Yangtze River mouth and implications for the depositional mechanisms - Niu, Wenlei; Nian, Xiaomei; Zhao, Luo; Zhai, Yang; Meadows, Michael E; Zhang, Wentong; Wang, Zhanghua (Frontiers in Earth Science, 2022)
Muddy sediments are the most prominent constituents of sedimentary successions in tide-dominated river mouths and have highly complex depositional mechanisms. In this study, we performed fine-grained (4–11 μm) quartz OSL dating on two sediment cores collected at a shipwreck site in the turbidity maximum zone (TMZ) of the modern Yangtze River mouth, China, which were compared with previously published dating results (45–63 μm quartz OSL dating, radionuclide dating, porcelain artifacts recovered from the wreck, macro-plastics, and the morphological history recorded in marine charts). We investigate the luminescence characteristics of muddy sediments trapped in the TMZ and discuss the implications of OSL ages in understanding depositional mechanisms in tide-dominated river mouths. The results indicate that most OSL ages of muddy sediments in the delta front setting are overestimated compared with other dating methods. We suggest that OSL age overestimation reflects the trapping of marine-sourced sediments in the TMZ imported by saltwater intrusions and storm events. The marine-sourced sediments contain high percentages of residual luminescence and are also subjected to incomplete bleaching due to turbid water conditions and near-bed dispersal in the partially mixed stratified river mouth. We thus suggest that the reduced bleaching efficiency of muddy sediments in delta front settings needs to be accounted for in understanding sedimentary processes and distinguishing between different sedimentary facies in tide-dominated river mouths. Furthermore, we propose that differences in quartz OSL ages of fine- and medium-grained fractions may arise in response to extreme events.